THE SIGNIFICANCE OF VICTORIAN PERIOD IN ENGLISH PROSE (Scientific journal of the Fergana State University, 2024)
The Victorian era was marked by the discovering of railways, trains, steamships for the first time in the world, the introduction of mining and industrial use of steel, coal, iron, the emergence of new markets, the development of science. What is more, it is the important period for the English literature with the introduction of realism.This article deals with the features of Victorian literature, its writers, novel which is considered the main literary genre of this period, as well as its themes. A number of social changes and factors that led to the emergence of literary realism of the Victorian era have been studied. The impact of the industrial revolution and upheavals on English literature was highlighted.